A Differentially Driven Dual-Polarized Dual-Wideband Complementary Antenna for 2G/3G/LTE Applications. (2nd June 2014) - Feng, Botao; Li, Shufang; An, Wenxing; Hong, Weijun; Yin, Sixing
Abstract : A novel differentially driven dual-polarized dual-wideband complementary patch antenna with high isolation is proposed for 2G/3G/LTE applications. In order to generate dual-polarization and dual-wideband properties, a pair of biorthogonal dual-layer η -shaped tapered line feeding structures is utilized to feed two pairs of dual-layer U-shaped patches, respectively. The upper-layer U-shaped patches mainly serve the upper frequency band, while the lower-layer ones chiefly work for the lower frequency band. Besides, a horned reflector is introduced to improve radiation patterns and provide stable gain. The prototype antenna can achieve a bandwidth of 25.7% (0.78 GHz–1.01 GHz) with a stable gain of 7.8 ± 0.7  dBi for the lower band, and a bandwidth of 45.7% (1.69 GHz–2.69 GHz) with a gain of 9.5 ± 1.1  dBi for the upper band. Input isolation exceeding 30 dB has been obtained in the wide bandwidth. Thus, it can be potentially used as a base station antenna for 2G/3G/LTE networks.